Gagasan Abdurrahman Wahid Tentang Pengembangan Pendidikan Pesantren (1970-1980) - Untung, Moh. Slamet (UIN Walisongo, 2016)
The major problem of this article is how Abdurrahman Wahid’s ideas on developing pesantren education. It is elaborated into major sub-problems, namely the pesantren existence in the political frame of the New Order in the decades of 1970s and 1980s, Abdurrahman Wahid’s view on pesantren, and on the framework of developing pesantren education. This research is designed as qualitative one using hermeneutic and content analysis approaches. The findings of this research show that the phenomena of inability of pesantren in facing the New Order power, the policies of non pro-pesantren regime, and political suppression and systematical marginalization to pesantren done by the New Order regime in the decades of 1970s and 1980s became the factors that opened the way for the emergence of pesantren educational development ideas. Meanwhile, the common manifestations of the stagnant and …